2020
DOI: 10.3389/fchem.2020.605343
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4 Modified by meso-Tetrahydroxyphenylchlorin for Photocatalytic Hydrogen Evolution Under Visible/Near-Infrared Light

Abstract: A new photocatalyst denoted as mTHPC/pCN was prepared by modifying protonated graphitic carbon nitride (pCN) by meso-tetrahydroxyphenylchlorin (mTHPC). Relevant samples were characterized via various methods including zeta potential measurements, X-ray diffraction, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, N 2 adsorption-desorption, transmission electron microscopy, ultraviolet-visible-near-infrared spectroscopy, electrochemical impedance spectroscopy, photocurrent response mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 110 publications
(114 reference statements)
1
11
0
Order By: Relevance
“…In order to show the enhanced charge separation in the fabricated CuO/g-C 3 N 4 composite, PL spectra were obtained, as shown in Figure 9 . As can be observed, an emission peak of g-C 3 N 4 is located at 460 nm, which agrees with the previous results ( Liu and Ma, 2020 ; Zhang M. et al, 2021 ). The intensity of PL peak is high in case of g-C 3 N 4, which shows poor charge separation.…”
Section: Resultssupporting
confidence: 93%
“…In order to show the enhanced charge separation in the fabricated CuO/g-C 3 N 4 composite, PL spectra were obtained, as shown in Figure 9 . As can be observed, an emission peak of g-C 3 N 4 is located at 460 nm, which agrees with the previous results ( Liu and Ma, 2020 ; Zhang M. et al, 2021 ). The intensity of PL peak is high in case of g-C 3 N 4, which shows poor charge separation.…”
Section: Resultssupporting
confidence: 93%
“…The catalysts with and without Pt were systematically tested and characterized to understand the role of D149 and Pt. Previous studies using Pt as a cocatalyst demonstrated the presence of Pt particles on g-C 3 N 4 by using TEM and EDX mapping [31,[40][41][42]. The presence of Pt particles was found to enhance the absorption of visible light and photocatalytic activity [31,[40][41][42].…”
Section: Introductionmentioning
confidence: 93%
“…For a dyesensitized photocatalyst, the dye molecules adsorbed on the surface of a semiconductor can be excited after absorbing visible light, thus injecting electrons into the conduction band of the semiconductor. MK2/TiO 2 [33], Eosin Y/TiO 2 [34], N749/rGO [35], GS12/TiO 2 [36], PY-1/g-C 3 N 4 [37], PY-2/g-C 3 N 4 [37], ZnPy/g-C 3 N 4 [38], chlorin e6/g-C 3 N 4 [39], protoporphyrin/g-C 3 N 4 [40], mTHPC/g-C 3 N 4 [41], Ppa/g-C 3 N 4 [42], N3/g-C 3 N 4 [31], and N719/g-C 3 N 4 [31] exhibited enhanced performance in H 2 evolution. How-Processes 2021, 9, 1055 2 of 15 ever, more studies are needed to enrich the family of dye-sensitized g-C 3 N 4 , to find more efficient catalysts for water splitting, and to understanding fundamental aspects of these photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we report a π -conjugated heptazine derivative, 2,5,8-tris(2,4-difluorophenyl)-1,3,4,6,7,9,9b-heptaazaphenalene (HAP-3DF), which exhibits enhanced EL by exploiting n→ π * transitions and exciplex-based TADF, respectively. On the basis of the planar and comparatively rigid heterocyclic system with six C=N bonds surrounding a sp 2 -hybridized N atom of the heptazine core, heptazine derivatives have aroused widespread attention over the past decade by virtue of charming optical, photocatalytic as well as electronic properties in the fields of hydrogen evolution, organic optoelectronic technologies and so forth ( Ge et al, 2013 ; Li et al, 2013 ; Ou et al, 2017 ; Liu and Ma, 2020 ). Considering the strong electron-accepting ability of HAP-3DF, bis(2-(diphenylphosphino)phenyl) ether oxide (DPEPO) with two electron-accepting diphenylphosphine oxide groups was chosen as the host material.…”
Section: Introductionmentioning
confidence: 99%